OPTIMEX: Measurement of Detonation Velocity with a Passive Optical Fibre System - Pachman, Jiří; Künzel, Martin; Kubat, Karel; Šelešovský, Jakub; Marsalek, Roman; Pospisil, Martin; Kubicek, Michal; Prokes, Ales (Institut Przemyslu Organicznego, 2017)
Detonation velocity (VOD) is one of the most important parameters describing the detonation process of a particular explosive. This article summarizes some peculiarities that we have come across when building and testing our new passive optical VOD meter - OPTIMEX. The advantages of using multiple probes with independent signal recording is discussed. The practical issues related to an explosive's translucency are solved. Finally, a new method for detonation velocity data evaluation is proposed and demonstrated.
OPTIMEX: Měření detonační rychlosti pasivním vláknovým systémem
Keywords: velocity of detonation; VOD; optical fibre; passive VOD measurement; OPTIMEX; detonační rychlost; VOD; optické vlákno; pasivní měření VOD; OPTIMEX